2012
DOI: 10.1149/2.014208jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of 4-Morpholinoaniline in Nonaqueous Solvents

Abstract: Electrochemical oxidation of 4-morpholinoaniline (4MA) in six nonaqueous solvents was carried out using cyclic voltammetry technique. Two one-electron transfer couples were observed with a half-wave potential separation ( E 1/2 ) which is consistent with the donor number of solvents. In these solvents, in scan rates (0.1-1 Vs −1 ), the first oxidation step of 4-morpholinoaniline was found to be diffusion controlled with chemically reversible process. Significant differences in the chemical reversibility were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…It is well known that, the reduction mechanism of an organic compound changes from the one two-electron step in a protic to the two one-electron steps in an aprotic environment. 26,27 So, it can be concluded that, the two-electron reduction of 1 to 2 in aqueous solutions (Scheme 1), changes to the two successive one-electron transfer steps in [C4mim][BF4] (Scheme 7).…”
Section: Electrochemical Study In [C4mim][bf4]mentioning
confidence: 99%
“…It is well known that, the reduction mechanism of an organic compound changes from the one two-electron step in a protic to the two one-electron steps in an aprotic environment. 26,27 So, it can be concluded that, the two-electron reduction of 1 to 2 in aqueous solutions (Scheme 1), changes to the two successive one-electron transfer steps in [C4mim][BF4] (Scheme 7).…”
Section: Electrochemical Study In [C4mim][bf4]mentioning
confidence: 99%
“…On the other hand, despite the fact that significant efforts are devoted mainly to structural designing, the physical and chemical properties of CPs are also highly dependent on the polymerization conditions involving applied potentials, solvents, supporting electrolytes, current density, temperature and pH, as well as the method of electropolymerization. [18][19][20] For typical conducting polymers including polypyrrole, [21][22][23] polythiophene (inclusive of PEDOT) [24][25][26][27] and polyaniline, [28][29][30] effects of electropolymerization conditions on polymer films based on monomers have been substantially studied. It was reported that a small supporting electrolyte was easily dispersed in the polymer films to improve doping and contrast, and thus the electrochromic performances.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that cyclic voltammetry is a powerful technique for investigation of electrochemical reactions that are coupled with chemical reactions [13,14]. Electrochemical studies of amines were performed at various conditions such as aqueous and nonaqueous solvent or at various pHs [15][16][17][18][19][20][21]. Electrochemical oxidation mechanism of aromatic amines is quite complex, and leads to a variety of products depending on their structure and electrolysis conditions [22,23].…”
Section: Introductionmentioning
confidence: 99%